HOMOGENITAS WAJAH BIROKRASI DI ARAS LOKAL - Haboddin, S.IP, MA, Muhtar (Pusat Pelatihan dan Pengambangan dan Kajian Desentralisasi dan Otonomi Daerah Lembaga Administrasi Negara, 2010)
Empirical realities indicated that homogenization of bureaucratic features at local level was getting intense. The study reveals that homogenization became massive when ethnicity, family relation, and regionalism became dominant determinants in recruitment process as well as in determining structural position in local bureaucracy. This paper attempts to analyze homogenization of bureaucratic features of local bureaucracy. Perspective of nepotism and recruitment were selected in understanding the issues. Both are widely used in political studies and government administration sciences